THE STRUGGLE OF MAX TO REACH EQUALITY FOR LOW CLASS PEOPLE IN ELYSIUM MOVIE - SAPUTRA, ERANDHI HUTOMO (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Class Disparity, Class Struggle, Resistance and Rebellion, Equality.The differences especially in social welfare affects to the disparity between classes. Marxist divided people into two classes, the bourgeoisie and the proletarian. The disparity makes a conflict between the bourgeoisie and the proletarian because of the inequality. Therefore the proletarians struggle against the bourgeoisie to reach the equality. The movie which portrays the struggle of proletarian to reach the equality is Elysium. Question arose on how one of the proletarians, Max, struggles to reach equality for low class people in Elysium movie? This study aims to add the reference of Marxist study which focuses on the struggling process by low class people to reach equality. To do the analysis, the writer employs Marxism as an approach accompanied with theory of resistance and rebellion, theory of equality, and film studies. Finally, the writer finds that in Elysium movie there are many inequality of life got by low class people. Because of the inequality, people are divided into two classes and separated by the planet that they live. The separating planets and the different treatments for low class people lead the conflict between those classes. Max as the proletarian also has a conflict with his boss and he decides to take an action of struggle through resistance and rebellion by uniting and constituting as a group with the other proletarians. After the action of struggle through resistance and rebellion, he finally gets the equality dreamed by low class people and lessens the social gap although he is sacrificing his life.The writer suggests the next researcher who is interested to analyze Elysium movie as an object to use theory of Eco-Criticism because the crisis of the environment and theory of Science Fiction because there are elements of fiction in Elysium movie.